2023
DOI: 10.3389/fped.2023.1055813
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity and neurodevelopmental outcomes in preterm infants: A systematic review and meta-analysis

Abstract: BackgroundRetinopathy of prematurity (ROP) and abnormal brain development share similar risk factors and mechanisms. There has been contrasting evidence on the association of ROP with adverse neurodevelopmental outcomes.ObjectiveWe analysed the association between ROP at levels of severity and treatment with all neurodevelopmental outcomes until adolescence.Data sourceWe followed PRISMA guidelines and searched Medline and Embase between 1 August 1990 and 31 March 2022.Study selection and participantsRandomised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Two recent systematic reviews concluded that there was an association between bevacizumab and adverse neurodevelopmental outcomes, such that new safety studies were required including long term follow up. 10 , 11 All anti-VEGF agents move quickly into the systemic circulation after intravitreal injection, but bevacizumab and aflibercept appear to be cleared more slowly from the circulation with resultant suppression of VEGF levels. 28 We have confirmed the rapid clearance of ranibizumab and lack of effect on VEGF levels in the RAINBOW population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent systematic reviews concluded that there was an association between bevacizumab and adverse neurodevelopmental outcomes, such that new safety studies were required including long term follow up. 10 , 11 All anti-VEGF agents move quickly into the systemic circulation after intravitreal injection, but bevacizumab and aflibercept appear to be cleared more slowly from the circulation with resultant suppression of VEGF levels. 28 We have confirmed the rapid clearance of ranibizumab and lack of effect on VEGF levels in the RAINBOW population.…”
Section: Discussionmentioning
confidence: 99%
“…Such data are important as there remains concern that the suppression of systemic VEGF levels after intravitreal treatment might produce remote effects on somatic or neurological development. 6 For example, recent reports, 7 , 8 , 9 including two systematic reviews with meta-analysis, 10 , 11 have suggested that neuromorbidity may be more frequent after bevacizumab treatment. The two largest non-randomised studies 7 , 8 comprise the majority of included infants and may have been biased because anti-VEGF treatment was preferred in sicker and less mature infants, who would be expected to have higher rates of neurodevelopmental impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Premature delivery invariably results in very different neurodevelopment with effects lasting into adulthood [ 2 ]. Multiple complications such as necrotizing enterocolitis (NEC), bronchopulmonary dysplasia (BPD), late-onset sepsis (LOS), and retinopathy of prematurity (ROP), are independently associated with adverse neurological outcomes [ 3 , 4 , 5 , 6 , 7 ]. Preterm infants must adjust to extrauterine life without the caloric and nutritional supply from the placenta.…”
Section: Introductionmentioning
confidence: 99%
“…ROP deemed high risk for disease progression that could result in a poor visual or anatomic outcome (Type 1 ROP) is treated with laser photocoagulation and/or intravitreal anti-VEGF antibody (bevacizumab) [6]. Several studies have reported an association between laser photocoagulation and decreased visual acuity and a higher rate of myopia and astigmatism during childhood [7,8]. Infants received intravitreal bevacizumab treatment may experience reactivation of ROP [9].…”
Section: Introductionmentioning
confidence: 99%